Photoacoustic dose monitoring in clinical high-energy photon beams. (4th April 2019) - Giza, Olivia M; Sánchez-Parcerisa, Daniel; Sánchez-Tembleque, Víctor; Herraiz, Joaquin L; Camacho, Jorge; Avery, Stephen; Udías, José Manuel
Abstract: This work describes all stages of development (setup, optimization, performance, and first experimental measurements) of an acoustic sensor that can be used for range monitoring and dosimetry of clinical radiotherapy beams. The detection device consists of an ultrasonic transducer, a combination of preamplifiers and differential amplifiers with filtered outputs and a digital oscilloscope. Simulations of the experimental setup were carried out to study the optimal measurement geometry and choice of transducer. The dose distributions were calculated with the Monte Carlo code FLUKA, while the acoustic simulations were performed with the analytical wave transport code k-Wave. The temporal profiles of the dose pulses, in the order of μ s, were measured with a scintillating crystal coupled to a photomultiplier and used as input for the acoustic simulation. Measurements were performed in a Cyberknife™ radiosurgery beam and a TrueBeam unit. A lead block was submerged in water and placed partially or totally in the irradiation field in order to increase the acoustic signal. Photoacoustic signals were detected with both beams with the expected shape and time-delay, after the frequency response of the detection system was taken into account. The proposed setup can detect photoacoustic signals originating from the penumbra of the treatment fields after being processed with the appropriate image analysis tools.